A comprehensive review of titanium dioxide nanoparticles in cementitious composites - J. Jenima; M. Priya Dharshini; M.L. Ajin; J. Jebeen Moses; Krishna Priya Retnam; Krishna Prakash Arunachalam; Siva Avudaiappan; Ramon Francisco Arrue Munoz (Heliyon)
Nanomaterials are incorporated to improve the characteristics of conventional concrete materials. Among them, Titanium dioxide (TiO2) nanoparticles exhibit sustainable concrete features such as optimization of materials, improvement of structures, recycling, and innovative waste management in materials and processes. This paper thoroughly elaborates on the effect of TiO2 nanoparticles on the composites of cement which in turn modifies the physical, mechanical, and ability to resist any chemical action, climate change, and abrasion; Furthermore, this study emphasizes the small fragment size, increased surface area and photocatalytic properties of cementitious composites. The key parameters for choosing TiO2 nanoparticles encompass their strength, antimicrobial characteristics, and stability against external environmental factors, covering a wide range of compatibility issues and exploring the fundamental characteristics of the material imbibing in cement. The present review includes the basic features of TiO2 nanoparticles, their utilization in cement, the fabrication processes, and influential factors on the workability of concrete. The review also comprises the workability of fresh concrete, mechanical qualities related to compressive, flexural, and tensile strength, and durability variables such as electrical resistivity, permeability, carbonation resistance, freeze-thaw cycles, and sulfate attack resistance. The report further investigates the ideal dosage of TiO2 nanoparticles and compares it to other nanomaterials utilized in cementitious compositions. More importantly, it emphasizes nano-titanium dioxide's ability to deal with pollutants in urban areas, notably nitrogen oxides (NOx), via its photocatalytic characteristics. The study explains how nano-TiO2 affects the microstructure of cement-based materials, resulting in improved durability, performance, and mechanical characteristics. Finally, this study outlines present problems and recommends future research using nano-TiO2 in cement-based materials.